The Effect of Work-Life Balance and Workload on Employee Performance with Motivation as a Mediating Variable - Yuliani, Reni; catur Widayati, Christina (Journal Economic Business Innovation, 2025)
Purpose: This study aims to examine the influence of Work-Life Balance and workload on employee performance, with work motivation as a mediating variable, among employees at RSUD.Method: The research was conducted with a population of RSUD Cengkareng employees, from which 92 respondents were selected using the Slovin formula. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach.Findings: The results indicate that Work-Life Balance and workload significantly and positively affect work motivation. Work motivation, in turn, significantly enhances employee performance. Moreover, Work-Life Balance has a significant direct effect on performance, whereas workload does not show a significant direct effect. Mediation testing reveals that work motivation fully mediates the relationship between workload and performance, and partially mediates the relationship between Work-Life Balance and performance.Novelty: This study provides empirical evidence on how motivation functions as both a full and partial mediator, offering nuanced insights into the interplay between Work-Life Balance, workload, and performance within a healthcare context.Implications: The findings suggest that management at RSUD should strengthen work-life balance policies and motivational strategies to improve employee performance, while also addressing workload issues through motivation-enhancing interventions.